Steam Education - An Important Factor that Increases the Effectiveness of Teaching Technology (Journal of Pedagogical Inventions and Practices, 2023)
In the context of new technological changes, training on the basis of STEAM education in general secondary education schools forms basic competencies and worldviews in students, which will be necessary when developing creativity and labor skills, in which the stage of afterschool education or a step towards an independent life. This article highlights the essence of STEAM educational technology, the importance of using STEAM education in the effective organization of technology science training and in the training of highly qualified, professional specialists who contribute significantly to the development of society and the state